EVALUATION OF 2013 CURRICULUM IMPLEMENTATION AT CIPULIR 01 STATE ELEMENTARY SCHOOL, SOUTH JAKARTA - Dian Ayu PRATIWI (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2022)
This study aims to evaluate the implementation of the SD Negeri Cipulir 01 Jakarta Selatan 2013 course. This type of research is descriptive research using qualitative methods. Use interview, observation and recording techniques for data collection. The evaluation model used is the evaluation model of Stake Countenance Model. Analyze data through data simplification, data presentation and drawing conclusions. The technique for checking the validity of data uses triangulation. The results show that in the learning preparation activities, teachers compiled RPP by downloading the lesson plans adapted to school conditions provided on the website of the Ministry of Education and Culture. In the implementation of the 2013 curriculum learning, teachers implemented comprehensive theme learning, adopted a scientific learning method, and adopted a learning model that was in line with the 2013 curriculum philosophy. In learning activities the methods used by the teacher have varied, but are still familiar with conventional learning methods. In the 2013 Curriculum learning assessment, teachers have used authentic assessments to assess the competence of students' attitudes, knowledge and skills. Authentic assessments used by teachers include observations, assessment discussions, performance, portfolios and written. There are several obstacles faced from adjusting the use of methods, lack of school facilities, and evaluations which are quite burdensome for teachers. The making of report cards is also an obstacle due to the teacher's lack of ability to describe an assessment and in the use of technology.